(untitled) (Journal of Vishwa Adarsha College, 2024)
This study aims to explore headteachers’ perspectives and practices on transformative learning in schools for their and teachers’ professional growth and effective learning of students. We used narrative inquiry as a research methodology for interpreting headteachers’ experiences. The first author interviewed three headteachers leading the secondary level. Collected data were transcribed, coded, categorized, thematized, and interpreted with the help of literature. The research found that headteachers possessed the conceptual ideas for transformative learning and practiced it in their schools. Critical self-reflection, collaborative learning, and experiential learning were some of the techniques used to practice transformative learning in schools. They need to empower teachers more on the curriculum so they plan and design projects in a communicative approach.